2016
DOI: 10.1167/16.14.12
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of gaze-centered and object-centered coding in a double-step saccade task

Abstract: The position of a saccade target can be encoded in gazecentered coordinates, that is, relative to the current gaze position, or in object-centered coordinates, that is, relative to an object in the environment. We tested the role of gaze-centered and object-centered coding in a double-step saccade task involving the Brentano version of the Müller-Lyer illusion. The two visual targets were presented either sequentially, requiring gaze-centered coding of the second saccade target, or simultaneously, thereby prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A second example of visual contextual effects that were robust for an intervening saccade was obtained by de Brouwer and colleagues 19 . In their study, participants were presented with a Brentano version of the Müller-Lyer illusion and had to make a memory-guided saccade from one endpoint of the illusion to the middle vertex.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A second example of visual contextual effects that were robust for an intervening saccade was obtained by de Brouwer and colleagues 19 . In their study, participants were presented with a Brentano version of the Müller-Lyer illusion and had to make a memory-guided saccade from one endpoint of the illusion to the middle vertex.…”
Section: Introductionmentioning
confidence: 88%
“…However, a single saccade from the intervening saccade target to the vertex was not influenced by the illusion, suggesting that the perceived direction between the first and second targets of the double-step saccade sequence was not affected by the illusion. de Brouwer and colleagues 19 concluded that the illusion biased the saccade plan made before the start of the saccade sequence and that biased plan was updated across the first saccade.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if the two targets were presented simultaneously instead, the brain could also code the dimensions of the second saccade based on the allocentric information about the location of the second saccade target relative to the first, which should result in an accurate second saccade. But this is not what happened (de Brouwer, Medendorp, & Smeets, 2016). The illusion caused systematic errors in the endpoint of the second saccade, irrespective of whether the targets were presented sequentially or simultaneously.…”
Section: Track the Dotmentioning
confidence: 96%